Protestants and mysticism in Reformation Europe
1 online resource.
Keywords: Edited by Ronald K. Rittgers and Vincent Evener, Protestants and Mysticism in Reformation Europe offers an expansive view of the Protestant reception of medieval mysticism, from the beginnings of the Reformation through the mid-seventeenth century. Providing a foundation and impetus for future research, the chapters in this handbook cover diverse figures from across the Protestant traditions (Lutheran, Reformed, Radical), summarizing existing research, analysing relevant sources, and proposing new directions for study. Each chapter is authored by a leading scholar in the field. Collectively, Protestants and Mysticism in Reformation Europe calls for a comprehensive reassessment of the relationship of Protestantism to its medieval past, to Roman Catholicism, and to the enduring mystical element of Christianity.